Human Metapneumovirus: An Emerging Respiratory Virus - Chand, Sonal; Karmacharya, Ranjita; Magar, Sabita Thapa; Nongmeikapam, Helena; Liangkiuwiliu, Ringkangmai; Talagatoti, David Ratna Paul (National Journal of Community Medicine, 2025)
Human metapneumovirus (hMPV), a significant yet often overlooked respiratory pathogen, causes mild to severe respiratory infections, particularly in children, the elderly, and immunocompromised individuals. Discovered in 2001, hMPV is now recognized globally as a leading cause of acute respiratory infections (ARIs) and severe acute respiratory illness (SARI). It spreads through respiratory droplets and exhibits seasonal peaks, often in winter. Studies in India, such as Chennai’s 2016–2018 surveillance, detected 4% positivity in pediatric ARI cases, aligning with global rates (7–19%). However, India's dense population, high respiratory disease burden, and limited healthcare access pose unique challenges. Unlike the Northern Hemisphere’s winter peaks, India’s tropical climate may influence seasonality, while co-infections with RSV, influenza, and adenoviruses complicate diagnosis. The virus also poses risks for elderly individuals, given India’s rising burden of COPD and asthma. Despite advances in molecular diagnostics, routine hMPV testing remains limited, leading to underreporting. Diagnosis relies on real-time PCR, with multiplex RT-PCR enabling co-infection detection. While no vaccine is available, preventive measures include hand hygiene, respiratory etiquette, and isolating infected individuals. Early detection through clinical suspicion, laboratory testing, and imaging is crucial for effective management. Expanding surveillance and epidemiological studies is vital to understanding hMPV’s burden and guiding public health responses. Strengthening diagnostic capacity and awareness can help mitigate morbidity and mortality, particularly in high-risk populations in India.